Drug Administration Errors Between Anesthetists: The Burden in Libya - Dalal Almghairbi; Rachel Evley; Takawira Marufu (AlQalam Journal of Medical and Applied Sciences, 2024)
Safe medication preparation and administration is a key part of anaesthesia practice. While anaesthesia practice has become safer, some medication errors can be inevitable leading to devastating complications. There is limited data and research on anaesthesia medication errors in developing economies. This study aims to identify the occurrence of medication errors and examines the associated factors, incident reporting, and preventive measures taken by anaesthetist practitioners in Libya. This was a multicentre; cross-sectional survey study conducted at three tertiary teaching hospitals in Libya from January 1, 2023 to June 30, 2023. An online questionnaire was sent to potential participants. Data was analysed using Statistical Package for Social Science (SPSS). The findings are expressed as absolute numbers and percentages. 185 completed surveys were returned for analysis (response rate = 84.09%). Anaesthesia technician (90.8%) commonly does medication preparation. 37.8% of respondents experienced one medication error and did not cause any harm to patients. Heavy workload/long hours (18.4%) were identified as the most common contributor to medication error in the operating room. Nearly all respondents 151 (81.6%) strongly agreed that double-checking the medication before administration was the most crucial preventive measure against medication errors. No effective reporting systems were identified. The study results are valuable to implementing and disseminating potential medication error risk mitigation or preventive strategies in developing economies. Enhancing medication administration safety in clinical practice should be a priority for policymakers at local and national levels across all healthcare contexts. يعد تحضير الأدوية وإدارتها بشكل آمن جزءًا أساسيًا من ممارسة التخدير. وفي حين أصبحت ممارسة التخدير أكثر أمانًا، إلا أن بعض أخطاء الأدوية يمكن أن تكون حتمية مما يؤدي إلى مضاعفات مدمرة. هناك بيانات وأبحاث محدودة حول أخطاء أدوية التخدير في الاقتصادات النامية. تهدف هذه الدراسة إلى تحديد حدوث أخطاء الأدوية وفحص العوامل المرتبطة بها والإبلاغ عن الحوادث والتدابير الوقائية التي يتخذها ممارسو التخدير في ليبيا. كانت هذه دراسة مسحية متعددة المراكز ومقطعية أجريت في ثلاثة مستشفيات تعليمية في ليبيا من 1 يناير 2023 إلى 30 يونيو 2023. تم إرسال استبيان عبر الإنترنت إلى المشاركين المحتملين. تم تحليل البيانات باستخدام الحزمة الإحصائية للعلوم الاجتماعية . يتم التعبير عن النتائج كأرقام مطلقة ونسب مئوية. تم إرجاع 185 استبيانًا مكتملًا للتحليل (معدل الاستجابة = 84.09٪). يقوم فني التخدير (90.8٪) عادةً بإعداد الأدوية. واجه 37.8٪ من المستجيبين خطأً واحدًا في الدواء ولم يتسببوا في أي ضرر للمرضى. تم تحديد عبء العمل الثقيل/ساعات العمل الطويلة (18.4%) باعتباره المساهم الأكثر شيوعًا في حدوث خطأ في تناول الأدوية في غرفة العمليات. وافق جميع المستجيبين تقريبًا 151 (81.6%) بشدة على أن إعادة فحص الدواء قبل الإعطاء كان الإجراء الوقائي الأكثر أهمية ضد أخطاء الأدوية. لم يتم تحديد أنظمة إعداد تقارير فعالة. نتائج الدراسة قيمة لتنفيذ ونشر التخفيف المحتمل لمخاطر أخطاء الأدوية أو الاستراتيجيات الوقائية في الاقتصادات النامية. يجب أن يكون تعزيز سلامة إعطاء الأدوية في الممارسة السريرية أولوية لصناع السياسات على المستويين المحلي والوطني في جميع سياقات الرعاية الصحية